Problem Find the minimum value of \displaystyle { \frac{ ( x + \frac{1}{x} )^6 - ( x^6 + \frac{1}{x^6}) - 2}{(x+\frac{1}{x})^3 + (x^3 + \frac{1}{x^3} )} } and x \in \mathbf{R}  and x > 0

Discussion:

\displaystyle { \frac{ ( x + \frac{1}{x} )^6 - ( x^6 + \frac{1}{x^6}) - 2}{(x+\frac{1}{x})^3 + (x^3 + \frac{1}{x^3} )} }

= \displaystyle { \frac{ ( x + \frac{1}{x} )^6 - ( (x^3)^2 + (\frac{1}{x^3})^2) - 2}{(x+\frac{1}{x})^3 + (x^3 + \frac{1}{x^3} )} }

= \displaystyle { \frac{ ( x + \frac{1}{x} )^6 - ( (x^3)^2 + (\frac{1}{x^3})^2 + 2)}{(x+\frac{1}{x})^3 + (x^3 + \frac{1}{x^3} )} }

= \displaystyle { \frac{ ( x + \frac{1}{x} )^6 - ( (x^3)^2 + (\frac{1}{x^3})^2 + 2 \times (x^3) \times \frac{1}{x^3})}{(x+\frac{1}{x})^3 + (x^3 + \frac{1}{x^3} )} }

= \displaystyle { \frac{ {( x + \frac{1}{x} )^3}^2 - (x^3 + \frac{1}{x^3})^2}{(x+\frac{1}{x})^3 + (x^3 + \frac{1}{x^3} )} }

= \displaystyle { \frac{ {( x + \frac{1}{x} )^3 + (x^3 + \frac{1}{x^3})} {( x + \frac{1}{x} )^3 - (x^3 + \frac{1}{x^3})}}{(x+\frac{1}{x})^3 + (x^3 + \frac{1}{x^3} )} }

= \displaystyle { ( x + \frac{1}{x} )^3 - (x^3 + \frac{1}{x^3})}

= \displaystyle { 3( x + \frac{1}{x} )}

Applying Arithmetic Mean – Geometric Mean Inequality (since x is positive), we have:

\displaystyle { \frac {( x + \frac{1}{x} )}{2} \ge \sqrt {x\times \frac{1}{x}} = 1 }

\displaystyle { \Rightarrow ( x + \frac{1}{x} ) \ge 2 }

\displaystyle { \Rightarrow 3( x + \frac{1}{x} ) \ge 3\times 2 = 6}

Hence the minimum value is 6.

Chatuspathi: